Framing research on technology and student learning in the content area : implications for educators - Pechuekonis, Lynn; Schrum, Lynne; Thompson, Ann D. (Research methods in educational technology., 2008)
This book is a result of collaboration between NTLS and SITTE.Framing Research is targeted at individuals or small teams of educational researchers who are interested in conducting high quality research addressing the effects of technology-enhanced instruction on student learning. The book summarizes and unpacks the methodologies of a variety of research studies, each situated in the context of school subject areas, such as science, mathematics, social studies, and English/language arts, as well as in the contexts of reading education, special education, and early childhood learning. Taken together, the analyses provide guidance on the design of future technology research grounded in student learning of K-12 curriculum. The conclusions also serve as a tool for teacher educators seeking to prepare teachers to integrate technology effectively in their instruction and to motivate reluctant teachers to overcome perceived inconveniences connected with technology use.